Dependence between the quantum yield of chlorophyll a fluorescence in marine phytoplankton and trophicity in low irradiance level - Ostrowska, Mirosława (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
The paper presents the dependence of relative fluorescence quantum yield of marine phytoplankton on trophicity (as a measure of trophicity the chlorophyll a concentration was assumed). The dependence was worked out using the following empirical data from different regions of Southern Baltic: artificially excited phytoplankton fluorescence measured with BBE Moldaenke FluoroProbe and phytoplankton light absorption coefficient measured with spectrophotometer. The statistical analyzes allow establishing mathematical expression describing relation between fluorescence quantum yield and chlorophyll a concentration in sea water. This result can be useful in the future in the modeling of fluorescence quantum yield as a function of environmental factors.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 567-577
Keywords: optyka; marine optics; optical measurements in the photobiology; quantum yield of fluorescence; chlorophyll fluorescence; bio-optical modeling